Improving the uptake of preconception care and periconceptional folate supplementation: what do women think? - Chapman Anna; Mazza Danielle (BMC, 2010)
Abstract Background Despite strong evidence of the benefits of preconception interventions to improve pregnancy outcomes, the delivery and uptake of preconception care in general and periconceptional folate supplementation in particular remains low. The aim of this study was to determine women's views of the barriers and enablers to the uptake of preconception care and periconceptional folate supplementation. Methods Focus groups were undertaken in 2007 with 17 women of reproductive age (18-45 years). To identify key issues and themes within the data, focus groups were analysed using an inductive process of thematic analysis. Results Most women were unaware of the need to attend for preconception care and were surprised at the breadth of issues involved. Women also felt general practitioners (GPs) should be more proactive in promoting preconception care availability but acknowledged that they themselves had to be thinking about pregnancy or becoming pregnant to be receptive to it. Barriers to periconceptional folate supplementation included confusion about reasons for use, dose, duration, timing and efficacy of folate use. Enablers included the desire to do anything they could to ensure optimum pregnancy outcomes, and promotional material and letters of invitation from their GP to advise them of the availability and the need for preconception care. Conclusion A number of important barriers and enablers exist for women regarding the delivery and uptake of preconception care and periconceptional folate supplementation. It is essential that these patient perspectives are addressed in both the implementation of evidence based clinical practice guidelines and in the systematic design of an intervention to improve preconception care delivery.